Absence of Axoglial Paranodal Junctions in a Child With CNTNAP1 Mutations, Hypomyelination, and Arthrogryposis. (September 2018) - Conant, Alexander; Curiel, Julian; Pizzino, Amy; Sabetrasekh, Parisa; Murphy, Jennifer; Bloom, Miriam; Evans, Sarah H.; Helman, Guy; Taft, Ryan J.; Simons, Cas; Whitehead, Matthew T.; Moore, Steven A.; et al.
Leukodystrophies and genetic leukoencephalopathies are a heterogeneous group of heritable disorders that affect the glial-axonal unit. As more patients with unsolved leukodystrophies and genetic leukoencephalopathies undergo next generation sequencing, causative mutations in genes leading to central hypomyelination are being identified. Two such individuals presented with arthrogryposis multiplex congenita, congenital hypomyelinating neuropathy, and central hypomyelination with early respiratory failure. Whole exome sequencing identified biallelic mutations in the CNTNAP1 gene: homozygous c.1163G>C (p.Arg388Pro) and compound heterozygous c.967T>C (p.Cys323Arg) and c.319C>T (p.Arg107*). Sural nerve and quadriceps muscle biopsies demonstrated progressive, severe onion bulb and axonal pathology. By ultrastructural evaluation, septate axoglial paranodal junctions were absent from nodes of Ranvier. Serial brain magnetic resonance images revealed hypomyelination, progressive atrophy, and reduced diffusion in the globus pallidus in both patients. These 2 families illustrate severe progressive peripheral demyelinating neuropathy due to the absence of septate paranodal junctions and central hypomyelination with neurodegeneration in CNTNAP1 -associated arthrogryposis multiplex congenita.